2019
DOI: 10.2147/ijn.s192757
|View full text |Cite
|
Sign up to set email alerts
|

<p>Starch-mediated synthesis of mono- and bimetallic silver/gold nanoparticles as antimicrobial and anticancer agents</p>

Abstract: Background and aim: Bimetallic silver/gold nanosystems are expected to significantly improve therapeutic efficacy compared to their monometallic counterparts by maintaining the general biocompatibility of gold nanoparticles (AuNPs) while, at the same time, decreasing the relatively high toxicity of silver nanoparticles (AgNPs) toward healthy human cells. Thus, the aim of this research was to establish a highly reproducible one-pot green synthesis of colloidal AuNPs and bimetallic Ag/Au alloy nanoparticles (NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…15,18 Especially, low drug-resistant problems have generated using AuNPsrelated nanomedicines. 19 However, most of these AuNPs (5-100 nm) related medicines are still difficult to be cleaned from the body because of their large sizes. 20 The remaining gold is still a concern for safe medication.…”
Section: Introductionmentioning
confidence: 99%
“…15,18 Especially, low drug-resistant problems have generated using AuNPsrelated nanomedicines. 19 However, most of these AuNPs (5-100 nm) related medicines are still difficult to be cleaned from the body because of their large sizes. 20 The remaining gold is still a concern for safe medication.…”
Section: Introductionmentioning
confidence: 99%
“…164 As a consequence, great efforts have been made to establish green nanotechnology approaches in the field: from the use of bacteria or fungi as raw materials, to the employment of plant extracts or waste materials. 165,166 Therefore, these green NMs have been used in different applications in the biomedical field. 98,167 In terms of electroconductive NMs, not many examples have been recently released to literature, however, efforts toward this end have shown that the use of green practices can allow for a sustainable production of such NMs and their successful application within tissue engineering and regenerative medicine.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
“…Lomelí-Marroquín D. et al (2019) achieved the synthesis of bimetallic silver/gold nanoparticles, with the advantages of an increased biocompatibility, usually associated with AuNPs, and of a decreased toxicity of silver nanoparticles (AgNPs) [14]. The product exhibited a dose-dependent anticancer effect on melanoma cells in vitro [14].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%